2011
DOI: 10.4103/0019-5413.73657
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting the free fibular graft: A modified approach

Abstract: Background:The conventional technique of free non-vascularized fibular grafting is attended with some amount of morbidity and a long scar. We report a technique with little interference to the surrounding soft tissues to harvest more than one-third of whole length fibula.Patients and Methods:Thirty four patients of average age 23.5 years (range 8 to 51 years) having various pathologies like simple bone cysts (n=9), fibrous dysplasias (n=6), giant cell tumors (n=7), fracture non-union (n=10) and aneurysmal bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…38,39 Several recent studies have shown that FNFAs harvested by a minimally invasive technique had the same benefits as FNFAs harvested by the periosteum-preserving technique in the treatment of bone defects in children and adults. 4042 In the above-mentioned studies, complete regeneration of the donor site after FNFA harvesting was obtained in most patients. In the present study, the FNFAs were harvested by the periosteum-preserving technique and positioned into the bone cavity after resection of the tumor-like lesions in the femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Several recent studies have shown that FNFAs harvested by a minimally invasive technique had the same benefits as FNFAs harvested by the periosteum-preserving technique in the treatment of bone defects in children and adults. 4042 In the above-mentioned studies, complete regeneration of the donor site after FNFA harvesting was obtained in most patients. In the present study, the FNFAs were harvested by the periosteum-preserving technique and positioned into the bone cavity after resection of the tumor-like lesions in the femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…Complications when harvesting the fibular strut graft, such as common peroneal nerve damage, weakness of extensor hallucis longus, ankle instability, nonunion, and stress fracture have been reported [ 8 , 12 ]. In order to prevent intraoperative problems during fibular harvest, it is important to preserve at least 5 to 6 cm of the proximal and the distal parts of the fibula [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retaining the distal fibula can prevent adverse effects on the distal tibiofibular syndesmosis and the ankle joint [ 15 ]. In addition, we feel that the biological approach for harvesting long free nonvascularized fibular graft as proposed by Mukherjee et al reduces donor site morbidity and is safer than conventional approach [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different options of vascularized fibular graft have been developed: single vascularized fibular graft, double-barrel technique, and combined vascularized fibula and allograft reconstruction [ 4 , 35 , 36 ]. In adult patients, a fibular graft up to 25–26 cm can be harvested [ 21 , 37 ]. The proximal fibula and the lateral malleolus should be spared to maintain knee and ankle joint stability, protect the common peroneal nerve, and preserve weight-bearing capacity [ 9 , 21 , 33 , 35 , 37 ].…”
Section: Reconstruction Using Biological Materialsmentioning
confidence: 99%